ANALISIS MINAT BACA SISWA DI PERPUSTAKAAN SDN 37 PEKANBARU - Pahrurrazi Pahrurrazi; Otang Kurniaman; Mahmud Alpusari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research was based on the background of students' interest in reading at the SDN 37 Pekanbaru library. This study aimsto determine (1) the willingness to read students; (2) student reading needs; (3) the act of reading students; In this study, thefocus of the research was students and librarians of SDN 37 Pekanbaru. Methods of data collection using closedquestionnaires, observation, documentation and unstructured interviews. Data analysis techniques use statistical methodswith percentage formulas and analysis of interview results. The results showing the aspects (1) the readability of students ofSDN 37 Pekanbaru in the library was well known; (2) the reading needs of students of SDN 37 Pekanbaru in the library arewell known; (3) the act of reading students from SDN 37 Pekanbaru in the library is well known.